Efficacy of LLLT in swelling and pain control after the extraction of lower impacted third molars - Merigo, Elisabetta (Laser Ther, 2015)
Introduction and aim: Low Level Laser Therapy (LLLT) can facilitate wound healing stimulating a more rapid resolution and an earlier start for the proliferation phase. The purpose of this study is to evaluate the effects of LLLT on postoperative pain and oedema following the removal of impacted lower third molars. Materials and methods: 1. 17 patients LLLT + traditional drug treatment; 2. 17 patients traditional drug treatment as control group; 3. 25 patients treated with LLLT only on one side+traditional drug treatment. The laser we have used for this study is a diode laser, GaAs, which delivers both in the infrared band at the wavelength of 910 nanometers (pulsed and superpulsed source), and in the visible (continuous source) at the wavelength of 650 nanometers (red). LLLT was performed just after the intervention and approximately 12 hours after surgery delivering 240 J in 15 minutes with theoretical fluence values of 480 J/cm(2) and 31 J/cm(2) for every minute of irradiation. We considered and signed with a label constant landmarks on both sides of the face of each patient; measurements were taken: before the surgery, after the surgery right after the 1st laser treatment, after approximately 24 hours after the 2(nd) laser treatment. Results: We collected all the values of the oedema measurements and the VAS reports and performed a statistical analysis by means One-way Analysis of Variance (ANOVA) test: for the evaluated values (X, Y, Z) an extremely significant difference was found with p values of 0.003 for Y at the first evaluation (pre-12 hours) and less than 0.001 for the other evaluations. A significant result was obtained for VAS recorded at hospital discharge (p<0.0001). Conclusions: This study demonstrates that LLLT is effective on postoperative pain and oedema accelerating healing time and reducing patients distress.